Operational amplifier circuit building blocks for laboratory experiment - Leong, Zi Yu (2015)
This hardware project aims to design and implement building blocks using operational amplifiers for laboratory experiments. The analog computational building blocks that will be discussed are first and second order differential equations solver and simultaneous set of two linear equation equations solver. In a typical system, solving mathematical model of one or more differential equation and initial conditions are commonly sought after. Differential equations are used in solving social issues, financial analysis and in many other areas. Integration operations are used over differentiation operation because the computer signals are of real voltages and it may be corrupted by noise. Since integration has a tendency to average out due to its negative feedback, it is more precise to obtain a solution using an integration method. A differential equations solver consist of many small blocks such as the integrator, summer and inverter. In this project, we will explore how these small blocks can be integrate together to provide a solution to the first and second order differential equation. A combination of 2 summers were further explored to solve simultaneous equations. Results observed are validated with theoretical calculations to ensure accuracy due to the anomalies in the circuity.